Global Health Governance on Cruise Tourism: A Lesson Learned From COVID-19 - Hu, Zhengliang; Li, Wenwen (Frontiers in Marine Science, 2022)
Cruise tourism is becoming increasingly popular worldwide. However, the health and safety of thousands of cruise tourists have been put in jeopardy due to the COVID-19 pandemic. The refusal of cruise ships calling has been the most significant reason behind the health hazards faced by passengers. Moreover, some coastal States have decided to close their borders, leaving passengers to their own fate in the case of a COVID-19 outbreak on board. Situation analysis contributes to demonstrating obstacles encountered in public health governance on cruise tourism. Information is collected from official websites of governments and international organizations to investigate the reasons behind the non-compliance of these countries with the International Health Regulations (IHR) (2005). Academic literatures showcase different views on the necessity of revising the IHR (2005). Statistical analysis is used to assess core capacities required by the IHR (2005) of the coastal States. Coastal States reserve their rights to refuse foreign cruise ships to enter ports and to prevent the persons aboard from embarking or disembarking so long as conditions under Article 43 are met. However, some foreign cruise ships were directly refused to call by various coastal States without scientific evidence. This practice stems largely from the high risk of COVID-19 outbreaks in cruise ships and the resulting burden from the cruise pandemic response. Compared with improving IHR (2005), especially its dispute settlement mechanism, helping coastal States to boost their core capacities is more conducive to solving the problem of cruise public health governance. The improvement of core capacities can be carried out from the aspects of surveillance of cruise ships and risk assessment, medical examinations on cruise travellers, cruise design and cruise tourism management.